EKSTRAKSI ASAM LEMAK OMEGA - 3 DARI LIMBAH IKAN TUNA - Jos, Bakti (METANA, 2006)
Abstract Tuna waste still have a valuable substance that is fish oil, which contains omega-3 fatty acid. Omega-3 is polyunsaturated fatty acid, consist of two acid, eicosapentaenoic acid (EPA) and dokosahexanoic acid (DHA). Omega-3 fatty acid has many usefulness for human’s health, related to heart, retina, and brain function. This research is done to get omega-3 fatty acid from tuna waste by extraction method using n-hexane. The purposes of the research are to learn about variables that affect the product and decide the condition to get optimal product. The research method is making table and chart from the variables. The condition of the operation are : temperature ± 30oC, solvent n-hexane, KOH concentration is 40 gr/liter, and concentration of oil in feed is 0.068 gr/cc. The variables are : comparison of solvent and feed (10:4; 15:4; 20:4; 25:4; 30:4; 35:4) at period 1,5 jam, and period of extraction (0,5; 0,75; 1; 1,25; 1,5; 1,75 jam) at comparison of solvent and feed 30:4. The result shows that the optimal condition is reached at comparison of solvent and feed 30:4 and period of extraction 1,5 hour. The rendement is 24,76%. Key words : tuna, omega-3, extraction